Home sweet home! Repatriation, reintegration and land allocation in Afghanistan - Nassim Majidi (Revue des Mondes Musulmans et de la Méditerranée)
Since 2002, an estimated 6 million Afghan refugees have returned to their homeland. The world has witnessed the largest voluntary repatriation program in recorded history (Kronenfeld, 2011), with over 4.6 million returnees assisted by the Government of Afghanistanand the United Nations High Commissioner for Refugees (UNHCR). While in 2002 Afghanistan was synonymous with return, in 2012 Afghanistanis synonymous with a stalling voluntary repatriation process, growing numbers of internally displaced persons (IDPs) and trends of mixed migration, with families, men, and unaccompanied children leaving Afghanistan legally or irregularly in the hope of a better life elsewhere. In 2012, ‘hope’ is no longer synonymous with Afghanistan, nor with return, but with life outside of ‘home’, outside of Afghanistan. In a context of transition and changing migration patterns, increasing emphasis is nevertheless being placed on policies of return to and reintegration into Afghanistan. Central to this question of return is access to land, and the resources available on the lands where returnees settle. This paper discusses the return of refugees to Afghanistan and the strained relationship between refugee return, land allocation and reintegration, with reference to research conducted in Afghanistan between 2007 and 2012.